Using Multi Criteria Decision Making Approach to Determine the Control Priority of Gaseous Pollutants from the Economic - Environmental Perspective in a Combined Cycle Power Plant in 2017 - Taleb ASKARIPOOR; Fateme TANHA; Elahe KAZEMI; Mostafa MARZBAN (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: The development and growth of industrial activities, has made environmental pollution a global challenge. Environmental assessment is an important approach which in addition to examining the impact of environmental pollutants on human health and other living organisms can provide solutions for optimal decision making and set control priorities. Methods: In this study, due to the importance of the relationship between qualitative criteria, the hierarchical analysis method was conducted to determine the control priorities of gaseous pollutants. Document reviews, results of measuring pollutants at power plant, knowledge and experience of 20 experts in health, environment and industrial safety were utilized in order to select and evaluate SO2, NOX, CO2 and CO2 gases. Then, criteria of permissible exposure limits, social costs and consequences were used for pairwise comparisons. Finally, inconsistency coefficient was calculated to confirm the results and compatibility in assessments. Results: Results of this study showed that NOX with the final weight of 0.58 was regarded as the first priority, SO2 with the weight of 0.32 considered as the second priority, CO2 with the weight of 0.052 was set as the third priority and CO with the weight of 0.038 was regarded as the last priority. Conclusion: Multi criteria decision making techniques, using expert qualitative opinions and converting them into quantitative variables reduces uncertainty in choices and ambiguity in planning, and can be utilized as an acceptable approach in determining control priorities of environmental pollutants